Proyeksi Elastisitas Permintaan Telur Ayam Ras di Malang Raya - Febrianto, Nanang; putritamara, Jaisy aghniarahim (Faculty of Animal Science, Universitas Brawijaya, 2017)
The objective of the study was aimed to analyze the socio-economic factors of consumers on the demand of eggs and analyze the elasticity of egg demand in Malang Raya. The research was conducted in Malang regency, Malang city and Batu city. The research method was conducted by survey. The number of respondents was 150 people so that each region consists of 50 respondents. Data analysis using natural Cobb-Douglas’s logarithm. The results of the analysis showed that the factors that influence the elasticity of egg demand in Malang Raya were the price of laying egg, income, number of family, education and gender. Price elasticity on demand of chicken eggs was elastic with a value of -2.301. The value of income elasticity of chicken egg demand is 0.285 means that it was inelastic, then the egg of chicken was normal. The value of cross price elasticity between demand of chicken eggs against milkfish was -2,289 meaning that milkfish was a substitute for laying egg.